FALLOSTSINTIGRAPHY IN THE DIAGNOSIS OF VASCULOGENIC ERECTILE DYSFUNCTION - A. D. Kaprin; A. A. Kostin; D. K. Fomin; N. G. Kulchenko; D. P. Kruglov; F. Sh. Mangutov (Исследования и практика в медицине)
Erectile dysfunction (ED) requires a comprehensive, advanced diagnostics, as the judge the state of the microvasculature of the corpora cavernosa by ultrasound may indirectly.Purpose. To improve the diagnostic results of erectile dysfunction using falloscintigraphy.Materials and methods. We examined 56 men. All patients fulfilled the ultrasound study of penis itself and stimulated erections with pharmacological agents (prostaglandin E, 20 mg). We spent falloscintigraphy to identify the microcirculatory disturbances in the tissues of the penis.Results. Analysis of the questionnaire of erectile function demonstrated that in the group there were 4 (7.1%) patients with severe ED, 29 (51.7%) — with moderate ED, 23 (41.2%) — with mild erectile dysfunction. According to the ultrasound of the penis we registered signs of ED in 38 (67.9%): arterial — 24 (63.1%) patients, venous ED — 11 (28.9%) patients, mixed ED — 3 (8%). In 18 (32.1%) patients by ultrasound, we detected no structural pathology tissue of the penis, so we conducted additional tests — falloscintigraphy. Falloscintigraphy results showed that the two men (11.2%), we have not identified any pathology. Therefore we have regarded their erectile dysfunction as psychogenic. In 16 (88.8%) patients were detected during falloscintigraphy impaired microcirculation of the corpora cavernosa. The results of our study show that falloscintigraphy has a high sensitivity (91%) and specificity (94%) compared to the US (78% and 60%, respectively) in the diagnosis of disorders of the microcirculation of the corpora cavernosa of the penis.Conclusions. Falloscintigraphy may be used for the diagnosis of vasculogenic erectile dysfunction, if the ultrasound is not effective to detect microcirculatory disturbances of the corpora cavernosa.